Improving Language Learning for Students: An Innovative Approach to Developing German Language Materials at Level B1 - Hafniati, Hafniati; Ahmad Bengar Harahap; Nur Hanifah Lubis (Universitas Pendidikan Ganesha, 2025)
The low pass rate of students in the reading section of the Goethe Zertifikat B1 exam indicates that students still experience difficulties in understanding German reading texts. This requires innovative learning media that can improve reading skills and support student learning independence. This study aims to develop and test the effectiveness of Microsoft Sway-based learning media to improve students' reading ability (Lesen) at the B1 level of German. This study is a development research with a 4D design. The research subjects were students of the German Language Education Study Program. In contrast, the trial subjects consisted of 30 students in the individual and small group testing stages, and 52 students in the field testing stage. Data were collected through CEFR-based reading tests (pre-test and post-test), expert validation questionnaires (materials and media), and student response questionnaires, with validated instruments. Data analysis techniques included quantitative descriptive analysis and gain score tests. The results showed an increase in average scores. This media was considered very valid, practical, and effective by experts and users. This study concludes that Microsoft Sway learning media is effective in improving the reading ability of German texts at the B1 level of students. The implications of these findings indicate that the use of interactive digital media can be an innovative solution to overcome students' difficulties in understanding foreign language reading and strengthening 21st-century skills.